Native Americans and Social and Environmental Justice: Implications for Criminology - Lynch, Michael J. (Social justice, 2011)
The article examines health and medical literature to explore the social, economic, and environmental injustices experienced by Native Americans. According to the authors, environmental injustice is defined as excluding minority groups from environmental decision-making or exposing the groups to environmental hazards. Details are provided on the social and economic inequalities facing Native Americans, such as poverty, income unemployment, and a proximity to toxic hazards. In addition, information is provided on uranium mining and nuclear accidents that have impacted Native Americans.